ENGLISH PROMOTION ON INSTAGRAM TO PROMOTE SERULINGMAS BANJARNEGARA INTERACTIVE ZOO - Amirawati, Ika; Puspitasari, Indah (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2021)
The purposes of this study is to make English promotion content on Instagram account @serulingmas_zoo, to know the problem and to overcome the problems in making English promotion content on Serulingmas Banjarnegara Interactive Zoo’s official Instagram account. The data was collected through direct practice method, observation method, documentation method and interview method. There were five contents uploaded on Instagram, three photos in the feed, one video in the feed and one Insta story which includes bilingual promotion content. Several obstacles found in the making English promotion on Instagram such as writing short captions that include all the information needed, choosing the diction and writing bilingual captions. However, there are also solutions to overcome those problems such as writing effective sentences, looking for references and using conversational sentences. The engagement of English promotion on Instagram increased. It can be seen from the increasing number of likes in the posts.